A Novel Ecological Approach Reveals Early Executive Function Impairments in Huntington’s Disease - Júlio, Filipa; Ribeiro, Maria J.; Patrício, Miguel; Malhão, Alexandre; Pedrosa, Fábio; Gonçalves, Hélio; Simões, Marco; van Asselen, Marieke; Simões, Mário R.; Castelo-Branco, Miguel; Januário, Cristina (Frontiers in Psychology, 2019)
Introduction - Impairments in executive functions are common in neurogenetic disorders such as Huntington’s disease (HD) and are thought to significantly influence the patient’s functional status. Reliable tools with higher ecological validity that can assess and predict the impact of executive dysfunction in daily-life performance are needed. This study aimed to develop and validate a novel non-immersive virtual reality task (“EcoKitchen”) created with the purpose of capturing cognitive and functional changes shown by HD carriers without clinical manifestations of the disease (Premanifest HD), in a more realistic setting. Materials and Methods - We designed a virtual reality task with three blocks of increasing executive load. The performance of three groups (Controls - CTRL, Premanifest HD individuals - HP and Early manifest HD patients - HD) was compared in four main components of the study protocol: the EcoKitchen; a subjective (self-report) measure - “The Adults and Older Adults Functional Assessment Inventory – IAFAI”; the “Behavioural Assessment of Dysexecutive Syndrome battery – BADS”; and a conventional neuropsychological test battery. We also examined statistical associations between EcoKitchen and the other executive, functional and clinical measures used. Results - The HD group showed deficits in all the assessment methods used. In contrast, the HP group was only found to be impaired in the EcoKitchen task, particularly in the most cognitively demanding blocks, where they showed a higher number of errors compared to the CTRL group. Statistically significant correlations were identified between the EcoKitchen, measures of the other assessment tools, and HD clinical features. Discussion - The EcoKitchen task, developed as an ecological executive function assessment tool, was found to be sensitive to early deficits in this domain. Critically, in premanifest HD individuals, it identifies dysfunction prior to symptom onset. Further it adds a potential tool for diagnosis and management of the patients' real-life problems.